Answer:
x = 3 , y = -6 thus B is the Answer
Explanation:
Solve the following system:
{y - 0.18 x = -6.54
{-2.8 x - y = -2.4
In the first equation, look to solve for y:
{y - 0.18 x = -6.54
{-2.8 x - y = -2.4
y - 0.18 x = y - (9 x)/50 and -6.54 = -327/50:
y - (9 x)/50 = -327/50
Add (9 x)/50 to both sides:
{y = 3/50 (3 x - 109)
{-2.8 x - y = -2.4
Substitute y = 3/50 (3 x - 109) into the second equation:
{y = 3/50 (3 x - 109)
{-2.8 x - 3/50 (3 x - 109) = -2.4
-2.8 x - (3 (3 x - 109))/50 = (327/50 - (9 x)/50) - 2.8 x = 327/50 - 2.98 x:
{y = 3/50 (3 x - 109)
327/50 - 2.98 x = -2.4
In the second equation, look to solve for x:
{y = 3/50 (3 x - 109)
327/50 - 2.98 x = -2.4
327/50 - 2.98 x = 327/50 - (149 x)/50 and -2.4 = -12/5:
327/50 - (149 x)/50 = -12/5
Subtract 327/50 from both sides:
{y = 3/50 (3 x - 109)
{-(149 x)/50 = -447/50
Multiply both sides by -50/149:
{y = 3/50 (3 x - 109)
x = 3
Substitute x = 3 into the first equation:
{y = -6
{x = 3
Collect results in alphabetical order:
Answer: {x = 3 , y = -6